Impacts of Climate Change on Tibetan Inhabited Areas in Sichuan Province, China - LIN, YI; BAO, WEN (DEStech Transactions on Environment, Energy and Earth Sciences, 2017)
Tibetan inhabited areas in Sichuan Province are part of Qinghai–Tibet region which is a unique geographic zone due to its high altitude, sparse human population and prevalent pastoral system. In the past decades, the climate in the region is becoming warmer, and this has resulted in the retreating of most glaciers, the uplifting of the snow lines, permafrost degradation, meteorological disasters and related mountain disasters are becoming more severe and frequent. Climate change may directly and indirectly affect economic outcomes in the short to longer term; it also can lead to household impacts, as well as regional impacts.